Proses Pengambilan Keputusan Orang Tua dalam Memberikan Restu Pernikahan Anak (Studi Kasus pada Peristiwa Silariang di Kab. Gowa) - Fadilah, Nurul; Nurdin, Muh. Nur Hidayat; Zainuddin, Kurniati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In the Bugis-Makassar tradition, there are two forms of marriage, namely through the process of proposing (assuro) and through the process of making mistakes (annyala) which can end in elopement (silariang). Silariang is a marriage that is considered not to comply with the customary norms that apply in Makassar society, so it is usually difficult for the perpetrator to get the blessing of both parents. This research aims to obtain an overview of parents' decision-making process in giving blessings to children who perform silariang. The respondents in this study were two Makassarese parents who had daughters who did silariang. This research uses a qualitative type of research method with a case study method. This research uses semi-structured interviews as a data collection technique, by conducting triangulation and member checking as data validity techniques. The research results show that there are differences in the decision-making process by respondents, which are influenced by gender and thinking style. The implication of this research is that it can be used as material for self-introspection for parents in educating their children (especially parents who have children who are silariang perpetrators), as well as understanding themselves better in making decisions.